Exploring The Strategic Decision-Making Process Of Startup Founders Conducting Business Pivots When Facing Significant Decreases In Local Market Demand - Henik Hari Astuti; Ferby Claudia; Muhammad Firmansyah (International Journal of Social Sciences, 2026)
This research investigates the strategic decision-making process of startup founders who undertake business pivots in response to a significant decline in local market demand. In the volatile landscape of the digital economy, the ability to pivot is often a prerequisite for survival; however, the cognitive and organizational mechanisms behind this strategic shift—especially when triggered by shrinking local demand—remain under-explored in qualitative economic literature. This study aims to fill this gap by deconstructing how founders interpret market signals, evaluate existing resources, and ultimately decide to alter their core business models. Using a qualitative approach with a multiple-case study design, this research involved in-depth interviews with startup founders from various sectors who successfully or partially navigated a pivot within the last years. Data were analyzed using thematic analysis to identify recurring patterns in the decision-making process. The findings reveal that the decision to pivot is not merely a rational-economic response to declining revenue but is heavily influenced by "bounded rationality," where founders must balance empirical market data with intuition and stakeholder pressure. The study identifies three critical phases in the pivot decision-making process: Crisis Recognition, where founders distinguish between temporary market fluctuations and permanent structural shifts; Strategic Re-orientation, involving the search for "adjacent possibilities" or new market niches; and Resource Realignment, where existing capital and human resources are reconfigured to support the new direction. Furthermore, the research highlights that a "founder's psychological resilience" and "cognitive flexibility" act as crucial moderators in determining the speed and success of the pivot. The implications of this study are twofold. Theoretically, it extends the resource-based view (RBV) and dynamic capabilities theory by providing a granular look at the micro-foundations of strategic flexibility in small-scale entrepreneurial ventures. Practically, the results offer a strategic roadmap for startup founders and venture capitalists in managing market downturns. It suggests that institutional support and mentorship should focus not only on financial runway but also on enhancing the strategic decision-making frameworks of founders to foster long-term economic resilience in the face of local market volatility.